Developing drugs for treatment of atopic dermatitis in children (≥3 months to <18 years of age): Draft guidance for industry. Issue 3 (30th March 2018) - Siegfried, Elaine C.; Jaworski, Jennifer C.; Eichenfield, Lawrence F.; Paller, Amy; Hebert, Adelaide A.; Simpson, Eric L.; Altman, Emily; Arena, Charles; Blauvelt, Andrew; Block, Julie; Boguniewicz, Mark; Chen, Suephy; et al.
Abstract: Atopic dermatitis is the most common chronic skin disease, and it primarily affects children. Although atopic dermatitis (AD) has the highest effect on burden of skin disease, no high‐level studies have defined optimal therapy for severe disease. Corticosteroids have been used to treat AD since the 1950s and remain the only systemic medication with Food and Drug Administration approval for this indication in children, despite published guidelines of care that recommend against this option. Several clinical trials with level 1 evidence have supported the use of topical treatments for mild to moderate atopic dermatitis in adults and children, but these trials have had little consistency in protocol design. Consensus recommendations will help standardize clinical development and trial design for children. The Food and Drug Administration issues guidance documents for industry as a source for "the Agency's current thinking on a particular subject." Although they are nonbinding, industry considers these documents to be the standard for clinical development and trial design. Our consensus group is the first to specifically address clinical trial design in this population. We developed a draft guidance document for industry, Developing Drugs for Treatment of Atopic Dermatitis in Children (≥3 months to <18 years of age) . This draft guidance has been submitted to the Food and Drug Administration based on a provision in the Federal Register (Good Guidance Practices) .